Protocol for cell proliferation and cell death analysis of primary muscle stem cell culture using flow cytometry - Pauline Garcia; Orane Mercier; Jade Ravent; Fabien Le Grand (STAR Protocols)
Summary: Skeletal muscle is critically dependent on the function of muscle stem cells (MuSCs) for effective muscle repair following injury. Here, we detail a protocol for the isolation of primary muscle cells and subsequent analysis of proliferation capacity in vitro using EdU (5-ethynyl-2′-deoxyuridine) on fixed cells. We also describe a cell death analysis on living cells with the identification of early- and late-apoptotic cells, as well as necrotic cells, through the incorporation of propidium iodide and YO-PRO-1 staining.For complete details on the use and execution of this protocol, please refer to Garcia et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.